2023
DOI: 10.1007/s00359-023-01646-6
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila ezoana uses morning and evening oscillators to adjust its rhythmic activity to different daylengths but only the morning oscillator to measure night length for photoperiodic responses

Abstract: Animals living at high latitudes are exposed to prominent seasonal changes to which they need to adapt to survive. By applying Zeitgeber cycles of different periods and photoperiods we show here that high-latitude D. ezoana flies possess evening oscillators and highly damped morning oscillators that help them adapting their activity rhythms to long photoperiods. In addition, the damped morning oscillators are involved in timing diapause. The flies measure night length and use external coincidence for timing di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 91 publications
(133 reference statements)
0
1
0
Order By: Relevance
“…In a follow-up study, Vaze et al ( 2023 , this issue) concluded that the bimodal activity patterns in D. ezoana seem to be driven by an evening and, perhaps to a lesser extent, a morning oscillator. However, when testing for diapause induction they concluded that D. ezoana explicitly measures night length, which is in line with a single dampened oscillator driving diapause, thus an external coincidence timing model (Vaze and Helfrich-Förster 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a follow-up study, Vaze et al ( 2023 , this issue) concluded that the bimodal activity patterns in D. ezoana seem to be driven by an evening and, perhaps to a lesser extent, a morning oscillator. However, when testing for diapause induction they concluded that D. ezoana explicitly measures night length, which is in line with a single dampened oscillator driving diapause, thus an external coincidence timing model (Vaze and Helfrich-Förster 2016 ).…”
Section: Discussionmentioning
confidence: 99%